Meta-governance in the realm of voluntary sustainability standards : early experiences and their implications - Derkx, Boudewijn (UN US, 2013)
Reports on the results of a research project unidertaken in 2009-2010 that looked into the experiences of four private and public-private transnational meta-governance initiatives in the realm of voluntary sustainability standards. Summarises the four case studies, to then integrate their findings and distil some more general lessons and insights about the practice of meta-governance in this arena.